Psychometric properties of the Malay-version of Social Media Addiction Test (SMAT17): The International Test Commission Approach - Harun, Mohd Ferdaus; Nik Adnan, Nik Nur Ras Nur Ain; Maarif, Farrah Azzwa; Kamal, Khairun Nisa; Hanisofian, Sara Malyana (Universiti Kebangsaan Malaysia and Malaysian Psychological Association (PSIMA), 2024)
The over-reliance on social media platforms is a growing concern, as more people find it difficult to disconnect from their online lives and develop an addiction. To effectively combat this issue, it is imperative to employ validated assessment tools that accurately measure problematic usage behaviors. This study aimed to adapt and validate the Social Media Addiction Test (SMAT17) for use in a Malaysian context. The adaptation process adheres to the International Test Commission Guidelines (ITC) for translating and adapting a test. A sequential translation design encompasses forward-backward technique, committee approach, and panel review were employed to translate the test. A total of 12 bilingual translators and a psychometric expert involved in the translation process. The Malay-version of SMAT17 demonstrated construct, language, and cultural equivalence of the original version and employed for a small-scaled validation study. A total of N=437 respondents were recruited using a convenience sampling technique. Psychometric properties of the adapted SMAT17 were examined using the Partial Least Squares Structural Equation Modelling (PLS-SEM) approach. Results indicate that the Malay-version SMAT17 demonstrated a similar factor structure as conceptualized in the original instrument. All PLS-SEM measurement model criteria were fulfilled, including significant outer loading, high internal consistency reliabilities, AVE, and HTMT correlations. SMAT17 also demonstrated convergent validity with the Smartphone Addiction Scale-Short Version (SAS-SV), and discriminant validity with the Satisfaction with Life Scale (SWLS). The successful adaptation of the SMAT17 provides a valuable tool for researchers and practitioners to investigate and address social media addiction in Malaysia.